Chemical Waste Gases Distribution to the Atmosphere Today’s Vehicles of Transportation are Chemical Problems - Mirzoahmed qizi, Alimova Nargiza; Shuxradjonovna, O‘rinova Dilafruz; Vladimirovna, Zubkova Nasiba; Botir qizi, Shodmonova Diyora; Zufarovna, Mansurova Nuriniso (European Journal of Life Safety and Stability (2660-9630), 2023)
Today, nature conservation is becoming a global problem. Today’s toxic fumes from vehicles, which harm nature, are destroying the ozone layer. This article can be a basis against the release of all kinds of biochemical pollutants that poison the nature and answer all the questions that torment us.